LITERATURE, LOSS, AND SPIRITUAL AWAKENING: RECONSIDERING ADAM’S FIRST POEM - Zulayho ABDURAHMON (International Journal of Literature and Language Studies, 2026)
Annotation. This article is devoted to the origin of literature and the history of the first poem composed by Adam. Through this historical narrative, the article also examines the purpose and functions of literature.